Immediate effect of Sukha Pranayama: A slow and deep breathing technique on maternal and fetal cardiovascular parameters - Vasudevan Rajalakshmi Vasundhara; Ananda Balayogi Bhavanani; Meena Ramanathan; Seetesh Ghose; Ganesan Dayanidy (Wolters Kluwer Medknow Publications, 2018)
Aim: This pilot study was done to evaluate the immediate effect of Sukha Pranayama, a slow and deep breathing technique on maternal and fetal cardiovascular parameters. Subjects and Methods: Single session pre-post comparison was done for 10 min of Sukha Pranayama in 12 pregnant women in their 3rd trimester. The study participants were guided to breathe in and out in a slow and regular manner for a count of 4 s each. Maternal cardiovascular parameters, namely mean heart rate (MHR), systolic pressure (SP), and diastolic pressure (DP), were measured before and after the session and rate-pressure product (RPP) derived with the formulae. Fetal heart rate (FHR) was derived from the nonstress test tracing. Results: SP, MHR, FHR, and RPP reduced significantly after single session of Sukha Pranayama. The mothers reported that they felt more relaxed and also sensed active fetal movement while performing the pranayama. Discussion: Reduction in maternal cardiovascular parameters may be attributed to reduced sympathetic activity coupled with enhanced vagal parasympathetic tone. Reduction in RPP signifies reduced myocardial oxygen consumption and load on the heart as evidenced by previous studies. These changes in cardiac autonomic status may enhance placental circulation, leading to healthier fetal development. Conclusion: The present study reiterates the importance of yoga for the psychosomatic health of maternal-fetal unit as an add-on relaxation technique. We plan to develop this pilot study into a full-fledged evaluation of maternal and fetal wellbeing through yoga.